Enterprise Resource Planning (ERP) Use In SMEs In Elazig Organized Industrial Zone - Ayden, Cem; Bilgin, Ebru (Fırat University, 2020)
Businesses need more information, communication and technology to survive and succeed in an increasingly competitive environment. For this reason, the use of software systems in enterprises is becoming more widespread. ERP, which is one of the advanced information technologies, is a software system used to integrate business processes (purchasing management, inventory control, warehouse management, control management, finance / accounting, etc.). ERP provides integration between the units of the enterprise and provides access to the data entered once. This system not only solves many of the problems faced by the enterprise, but also brings together many problems such as cost loss when not implemented successfully in the enterprise. The ERP system provides businesses with fast and large-scale benefits. While these benefits range from cost savings to increased productivity; it also makes it possible to bring a much more effective and faster decision mechanism to the management level. In this study, it is aimed to present basic information about small and medium sized enterprises operating in Elazığ Organized Industrial Zone, to reveal the ERP usage rates and usage areas of these enterprises and to investigate whether they have awareness about related software.

İşletmelerin artan rekabet ortamında varlıklarını sürdürebilmeleri ve başarılı olabilmeleri için daha fazla bilgiye, iletişime ve teknolojiye ihtiyacı vardır. Bu sebeple işletmelerde yazılım sistemlerinin kullanımı giderek yaygınlaşmaktadır. Gelişmiş bilgi teknolojilerinden olan ERP, işletme ile ilgili süreçleri (satın alma yönetimi, envanter kontrol, depo yönetimi, kontrol yönetimi, finans/muhasebe vb.) entegre etmede kullanılan bir yazılım sistemidir. ERP, işletmenin birimleri arasında bütünleşme sağlamakla birlikte bir kere girilen verilere tüm birimlerin erişimini sağlar. Bu sistem işletmenin karşılaştığı birçok problemi çözmesinin yanı sıra, işletmede başarıyla uygulanmadığında maliyet kaybı gibi birçok sorunu da birlikte getirir. ERP sistemi işletmelere hızlı ve büyük ölçekli faydalar sağlar. Bu faydalar maliyet tasarrufundan, verimlilik artışına kadar uzanırken; aynı zamanda çok daha etkili ve hızlı bir karar mekanizmasını yönetim kademesine kazandırmayı mümkün kılar. Bu çalışmada Elazığ Organize Sanayi Bölgesinde faaliyet gösteren küçük ve orta büyüklükteki işletmelere yönelik temel bilgileri sunup, bu işletmelerin ERP kullanım oranlarını ve kullanım alanlarını ortaya koyup ilgili yazılımlara ilişkin farkındalık sahibi olup olmadıklarını araştırmaya odaklanılmaktadır.
ELAZIĞ ORGANİZE SANAYİ BÖLGESİNDEKİ KOBİLERDE KURUMSAL KAYNAK PLANLANMASI (ERP) KULLANIMI